A Study on Determination of Topographical Surface Changes by Image Processing Techniques - Mustafa Zeybek; İsmail Şanlıoğlu (Doğal Afetler ve Çevre Dergisi)
This study presents the use of Unmanned Aerial Vehicle (UAV) for monitoring movements on topographic surfaces. In the study, it is aimed to reveal surface movements with neighbouring and correlation relations in the images obtained at different times. The latest and most effective measuring technology of recent years is undoubtedly UAV. UAV images were used together with Global Navigation Satellite System (GNSS), which can produce solutions with centimetre accuracy to evaluate surface movements. Within the scope of this study, the individual details which are extracted automatically on the images obtained at certain time intervals, changes caused by various reasons on the topographic surface, were observed. By using the similarities and differences between orthomosaics obtained at different times with the same coordinate system, topographic surface properties on the images can be examined. Taşkent (Konya) province where landslide cases are seen as intense in the study area was selected. The orthomosaic and digital terrain model data obtained by UAV images were used to determine the horizontal and vertical direction of the surface movements. Planimetric displacements at 0.005 m/day and 0.004 m/day movements at vertical were determined.